Substance Use, Childhood Sexual Abuse and Sexual Risk Behavior among Women in Methadone Treatment - Cohen, Lisa R. (2009)
Substance use and a history of childhood sexual abuse have both been identified as risk factors for unprotected sex among women, yet questions remain as to how their combined influence may differentially affect sexual risk behavior. In the current study a Generalized Linear Mixed Model was used to examine the interaction effect between current cocaine and opioid use and a history of childhood sexual abuse (CSA) on number of unprotected sexual occasions (USO) in a sample of 214 sexually active women in outpatient methadone maintenance treatment programs. Results show significant interaction effects between drug use in the past 30 days and CSA on unprotected sexual occasions. These interactions, however, differ depending on type of drug used and CSA status. For women with CSA, an increase in days of cocaine use was significantly associated with an increase in USO, whereas an increase in number of days of opiate use was not significantly associated with an increase in USO. In contrast, for women who did not report CSA, an increase in number of days of cocaine use was associated with a significant decrease in USO and number of days of opiate use was significantly correlated with an increase in USO. Findings indicate that CSA is related to unprotected sexual occasions depending on drug type and severity of use. Women with childhood sexual abuse using cocaine are at particularly high risk for having unprotected sex, which suggests that this group of women should be specifically targeted for HIV prevention interventions.